2019
DOI: 10.1177/0269215519841417
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of frailty among acute stroke patients, and evaluation of method of assessment

Abstract: Objective:We aimed to determine prevalence of pre-stroke frailty in acute stroke and describe validity of a Frailty Index–based assessment.Design:Cross-sectional.Setting:Single UK urban teaching hospital.Subjects:Consecutive acute stroke unit admissions, recruited in four waves (May 2016–August 2018). We performed the assessments within first week and attempted to include all admissions.Main measures:Our primary measure was a Frailty Index, based on cumulative disorders. A proportion of participants were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 37 publications
2
53
1
2
Order By: Relevance
“…We found 10.4% of the study population to be frail and 58.6% pre-frail in hospital by using a modified version of the Fried phenotype model, while other studies have found higher frailty prevalence and lower pre-frail prevalence in acute stroke populations [19,20]. A possible explanation for this is that in the present study, participants with missing data on a modified Fried criteria were given 0 points indicating a robust score on that specific criterion, which could partly explain our findings.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We found 10.4% of the study population to be frail and 58.6% pre-frail in hospital by using a modified version of the Fried phenotype model, while other studies have found higher frailty prevalence and lower pre-frail prevalence in acute stroke populations [19,20]. A possible explanation for this is that in the present study, participants with missing data on a modified Fried criteria were given 0 points indicating a robust score on that specific criterion, which could partly explain our findings.…”
Section: Discussionmentioning
confidence: 51%
“…Frailty is characterised by reduced physiologic reserve, increased vulnerability to stressors, and multisystem dysregulation [16,17] with symptoms such as fatigue, decreased strength and endurance, and weight loss [18]. Two previous studies have shown the prevalence of frailty among acute stroke patients to be 24.9% [19] and 28% [20], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of frailty status is emerging as a signi cant predictor of outcomes in various medical disciplines, including cardiology (27,45), neurology (46,47), oncology (48), orthopedics (23), and surgery (49), as well as the senior population in general. Accordingly, the association between frailty and all-cause mortality has been investigated across different settings and populations.…”
Section: Discussionmentioning
confidence: 99%
“…The mRS was not developed as an index of frailty, although it correlates well with established indices of frailty. 4,7,22 Thus, this study relates closely to the work of Seamon et al 20 They took a large cohort of Medicare patients in the USA to explore the influence of frailty (using the Faurot frailty index) and stroke severity on discharge to an inpatient rehabilitation setting. Their logistic regression analysis found that non-frail and pre-frail patients, and frail patients with low stroke severity scores, were more likely to be discharged to inpatient rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Twenty-five to 28% of these patients are frail, while 51% are considered 'pre-frail', approximately double the incidence observed in the general inpatient population. [4][5][6] Frailty is a predictor of mortality, length of stay and functional recovery in the period following an acute stroke. 5,[7][8][9] Twelve to 15% of stroke patients will die during their presenting admission, although this number is falling in the UK.…”
Section: Introductionmentioning
confidence: 99%